Kebolehpercayaan Coaching Behavior Scale for Sport dan Sport Motivation Scale versi bahasa Melayu: satu kajian rintis - Mohd Noor, Nurhasni; Hassan, Mohamad Faithal; Syed Ali, Syed Kamaruzaman; Soh, Kim Geok; Seruti, Jane Francisca (Faculty of Education, University of Malaya, 2017)
This pilot study is aimed at identifying the reliability of Malay version of Coaching Behaviour Scale for Sport (CBS-S) and Sport Motivation Scale (SMS) questionnaire to be used to replace the English version. A total of 40 footballers (male = 20, female = 20) from the Pahang Malaysia Sports School between 13 and 17 years old (M = 13.66, SD = .74). Respondents completed the CBS-S and SMS questionnaires that have been translated into Malay Language. CBS-S is used to assess coaching behaviour while SMS is to measure the level of athlete motivation. Cronbach's alpha analysis has been used to find the reliability of the questionnaires used. The findings show that the high reliability value for CBS-S is .96 with item correlation, r = .82 to .94 while SMS shows sufficient reliability .79 with item correlation, r = .59 to .88. The findings from this pilot study showed that CBS-S and SMS is suitable to use for replacing the English version to measuring coaching behaviour and the level of athlete motivation in Malaysia for sports school athletes.